Absence, loss-of-function, or inhibition of Escherichia coli AcrB does not increase expression of other efflux pump genes supporting the discovery of AcrB inhibitors as antibiotic adjuvants. (13th December 2021) - Ciusa, Maria Laura; Marshall, Robert L; Ricci, Vito; Stone, Jack W; Piddock, Laura J V
Abstract: Objectives: To determine whether expression of efflux pumps and antibiotic susceptibility are altered in Escherichia coli in response to efflux inhibition. Methods: The promoter regions of nine efflux pump genes ( acrAB, acrD, acrEF, emrAB, macAB, cusCFBA, mdtK, mdtABC, mdfA ) were fused to gfp in pMW82 and fluorescence from each reporter construct was used as a measure of the transcriptional response to conditions in which AcrB was inhibited, absent or made non-functional. Expression was also determined by RT-qPCR. Drug susceptibility of efflux pump mutants with missense mutations known or predicted to cause loss of function of the encoded efflux pump was investigated. Results: Data from the GFP reporter constructs revealed that no increased expression of the tested efflux pump genes was observed when AcrB was absent, made non-functional, or inhibited by an efflux pump inhibitor/competitive substrate, such as PAβN or chlorpromazine. This was confirmed by RT-qPCR for PAβN and chlorpromazine; however, a small but significant increase in macB gene expression was seen when acrB is deleted. Efflux inhibitors only synergized with antibiotics in the presence of a functional AcrB. When AcrB was absent or non-functional, there was no impact on MICs when other efflux pumps were also made non-functional. Conclusions: Absence, loss-of-function, or inhibition of E. coli AcrB did not significantly increase expression of other efflux pump genes, which suggests there is no compensatory mechanism to overcome efflux inhibition and supports the discovery of inhibitors of AcrB as antibiotic adjuvants.